1995
DOI: 10.1080/09595239500185101
|View full text |Cite
|
Sign up to set email alerts
|

Reviewing the needs of unemployed youth in smoking intervention programmes

Abstract: In Australia, the impact of unemployment on adolescent smoking behaviour continues to present a major public health problem. Traditional prevention programmes in both primary and secondary schools appear to be achieving a delay in the onset of smoking. However, smoking rates of young people who are unemployed are unacceptably higher than those of in-school youth. This paper provides a review of the published literature, showing that there has been little effort to address smoking patterns or experiences of qui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1996
1996
2002
2002

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…number of authors have noted deficiencies in adolescent smoking cessation programmes, and have suggested improvements in their structure (Stanton et al, 1995;Albrecht et al, 1998;Sussman et al, 1999). However, in terms of programme impact it could be beneficial to address the impact of broader issues in adolescents' environments.…”
Section: Theoretical Considerations In Programme Developmentmentioning
confidence: 99%
See 2 more Smart Citations
“…number of authors have noted deficiencies in adolescent smoking cessation programmes, and have suggested improvements in their structure (Stanton et al, 1995;Albrecht et al, 1998;Sussman et al, 1999). However, in terms of programme impact it could be beneficial to address the impact of broader issues in adolescents' environments.…”
Section: Theoretical Considerations In Programme Developmentmentioning
confidence: 99%
“…It has also been suggested that social mores have undergone ''de construction'', which may have limited drug use in the past (United Nations International Drug Control Programme, 1997;Flay et al, 1998;Hu et al, 1998). A longitudinal study of adolescent smokers found that they had more respiratory and other health problems than non-smokers, a greater likelihood of regarding their health as due to chance, played less school sport, were more likely to have parents who sought assistance for their child's problems, greater use of alcohol, and more contact with police (Stanton et al, 1995).…”
Section: Theoretical Considerations In Programme Developmentmentioning
confidence: 99%
See 1 more Smart Citation